Comprehensive review of Korean Medicine registries 2015–2023 - Kim, Soo-Dam; Choi, Sunmi; Kim, Sungha (Frontiers in Medicine, 2024)
Background Despite the increasing popularity of Korean Medicine (KM), its scientific evidence faces scrutiny. Instead of randomized controlled trials, registries are favored to capture the real world of KM practice due to the difficulties associated with proper control and the holistic nature of the KM approach. This review aimed to examine the KM registries in detail, identify the scope and focus of studies within this field, and assess the research trends. Methods We conducted a comprehensive analysis of KM registries listed in trial registration platforms, covering records from their inception until the end of 2023. The selection criteria aimed to include studies focusing on various interventions related to KM, with data extraction focusing on study characteristics and outcomes measured. The analysis utilized descriptive statistics to summarize the findings. Results We identified a steady increase in registry studies (2015, one; 2023, seven). Musculoskeletal disorders were most studied (28%), aligning with patients’ demand. The involvement of 112 primary clinics and Quality of Life (QOL) as the predominant outcome in 14 (66.7%) registries demonstrates the positive impact on patient well-being and the critical role that primary clinics play in KM practice. Conclusion Our findings indicate a heightened interest and commitment to evidence-based KM practices. Future Registries should be implemented on a large scale, incorporating long-term follow-up encompassing primary clinics. This approach would enable a comprehensive evaluation of the effectiveness and safety of KM interventions, as well as offer valuable insights into the influence of KM on chronic conditions and QOL.